2016
DOI: 10.1080/13854046.2016.1259387
|View full text |Cite
|
Sign up to set email alerts
|

Early numeracy skills in preschool-aged children: a review of neurocognitive findings and implications for assessment and intervention

Abstract: Objectives: The goals are to 1) provide a review of the typical and atypical development of early numeracy; 2) present what is known about the neurocognitive underpinnings of early numeracy; and 3) discuss the implications for early assessment and intervention. Method: Studies on the development of typical and atypical early numeracy are reviewed with a particular focus on longitudinal findings including those from our work on spina bifida myelomeningocele. Implications of this research for assessment are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 119 publications
0
37
0
6
Order By: Relevance
“…But where we were able to measure ANS acuity, it did not differ very much between children from high-and low-SES households. It differed enough for us to measure, but not enough to matter much in everyday life (or in math class), and the difference seems very unlikely to be the source of the huge gaps we find in children's knowledge of spoken and written numbers already by age 4 (For related findings, see Geary & vanMarle, 2016;Merkley & Ansari, 2016;Raghubar & Barnes, 2017).…”
Section: Conclusion 4: the Ses Gap In Math Achievement Is A Gap In Symentioning
confidence: 93%
See 1 more Smart Citation
“…But where we were able to measure ANS acuity, it did not differ very much between children from high-and low-SES households. It differed enough for us to measure, but not enough to matter much in everyday life (or in math class), and the difference seems very unlikely to be the source of the huge gaps we find in children's knowledge of spoken and written numbers already by age 4 (For related findings, see Geary & vanMarle, 2016;Merkley & Ansari, 2016;Raghubar & Barnes, 2017).…”
Section: Conclusion 4: the Ses Gap In Math Achievement Is A Gap In Symentioning
confidence: 93%
“…The other number representations that may be relevant to early education are written numerals (Geary & vanMarle, 2016;Merkley & Ansari, 2016;Purpura & Lonigan, 2015;Raghubar & Barnes, 2017).…”
Section: Written Numbersmentioning
confidence: 99%
“…A recent meta-analysis further suggests that early number competence but not WM predicts calculation performance in at-risk children ( Peng et al, 2016a ). In addition, while math training programs were found to have the largest effects on early number competence, improving domain-general cognitive skills does not seem to transfer to enhanced mathematical achievement (see Raghubar and Barnes, 2017 ).…”
Section: Healthy Math Development: Interactions Between Domain-specifmentioning
confidence: 99%
“…Further, suggestions on what is needed in future research from an educational perspective are put forth. Previous reviews differ from this review in that other authors have analysed effective interventions (Kroesbergen and Van Luit 2003;Mononen et al 2014), employed a neuropsychological approach (Raghubara and Barnes 2017) or used different inclusion criteria regarding participants (Sinnakaudan et al 2016) (for more details see section Previous reviews). Based on a meta-analysis of six longitudinal studies, Duncan et al (2007) found that the strongest predictors of later school achievement were school-entry mathematics skills, which were argued to be more important than reading and attention skills.…”
Section: Introductionmentioning
confidence: 99%